Does Academic Burnout Alleviate or Exacerbate Internet Dependence in University Students with Depression and Anxiety? - Jiang S; Jia Q; Peng Z; Zhou Q; Yi Q; An Z (Neuropsychiatric Disease and Treatment)
Shijie Jiang,1,* Qiyu Jia,2,* Zhenlei Peng,1,* Qixuan Zhou,1 Qizhong Yi,1 Zhiguo An1 1Xinjiang Clinical Research Center for Mental Health, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, 830011, People’s Republic of China; 2Department of Trauma Orthopedics, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, 830011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qizhong Yi; Zhiguo An, Xinjiang Clinical Research Center for Mental Disorder, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, 830011, People’s Republic of China, Email qizhongyi@126.com; 37989344@qq.comPurpose: This study aims to investigate whether academic burnout alleviates or exacerbates internet dependence among college students with depression and anxiety. Moreover, it intends to construct a moderated mediation model to examine how academic burnout moderates the relationship between depressive and anxious emotions and internet addiction and how social support mediates this relationship to determine the psychological motivations underlying addiction.Methods: A questionnaire survey was conducted using the simple random sampling method, which yielded 757 valid responses (response rate: a 93.11% response rate). The sample included 274 males and 466 females, with an average age of 20.90 years (± 1.48). Hierarchical regression analysis was employed for data analysis.Results: Anxiety and depressive symptoms directly affect the internet dependence of university students and indirectly affect it through the mediating role of social support. Academic burnout moderates the relationship between negative emotions and internet addiction, with high levels of academic burnout potentially decreasing the internet dependence of students experiencing negative emotions. We proposed a psychological self-regulation mechanism theory, which posits that learned helplessness may intensify the emotional symptoms of anxiety and depression, which is reflected in reduced internet use behavior.Conclusion: High levels of academic burnout can exacerbate symptoms of depression and anxiety, significantly reducing students’ interest in activities. For these students, a decrease in internet addiction may not be a positive sign; instead, it could indicate worsened depression and anxiety. This finding underscores the need for close monitoring of and intervention implementation for college students experiencing high levels of burnout and symptoms of depression or anxiety.Keywords: academic burnout, internet addiction, depression, anxiety, social support